From accuracy to fluency: Exploring EFL teachers’ perceptions of speaking assessment in pesantren-based school context - Andina Silvi Amalia; Junaidi Mistar (Journal of Research on English and Language Learning (J-REaLL), 2026)
This study was motivated by the gap between the ideal framework of speaking assessment, which emphasizes grammatical accuracy as a primary indicator, and classroom practice in Islamic boarding schools (pesantren), where fluency and confidence are often prioritized over linguistic accuracy. Accordingly, this study explores EFL teachers’ perceptions of grammatical accuracy in speaking assessment and how these perceptions influence the design and implementation of assessment rubrics. Employing a descriptive qualitative approach, data were collected through semi-structured interviews with three EFL teachers teaching at the elementary, intermediate, and advanced levels. The findings reveal that although grammatical accuracy is acknowledged as important, teachers tend to prioritize effective communication, fluency, and speaking confidence. The assessment rubrics applied are flexible and adapted to students’ backgrounds, proficiency levels, and learning needs. The study also confirms that teachers’ prior learning experiences, professional training, and personal beliefs significantly shape their assessment practices. However, the limited number of participants and the specific institutional context restrict the generalizability of the findings. The study highlights the importance of teacher training that promotes a holistic and contextual approach to speaking assessment, as such an approach may enhance learners’ communicative confidence, reduce speaking anxiety, and foster more active participation in English use within the pesantren environment. Future research is recommended to examine the long-term effects of improved speaking assessment practices on graduates’ social engagement and future opportunities.